Influence Incentive And Motivation To Performance Civil Servants In North Tapanuli Food Security Office - Vitria Tampubolon (Citakonsultindo, 2023)
This research aims to provide the influence of incentives and motivation on the performance of government employees. This research uses quantitative methods. The sample in this study used 59 government employees at the North Tapanuli Food Security Service. This research uses statistical analysis consisting of validity and reliability tests, classical assumption tests, and multiple linear tests. The data was run using SPSS version 20 software . The research results showed that incentives had a positive effect on the performance of government employees, but not significantly. The research results also show that motivation has a positive and significant effect on the performance of government employees. Then the test results also prove that incentives and motivation simultaneously have a positive effect on the performance of government employees at the North Tapanuli Food Security Service. In this case, may state civil servants use incentives to increase employee motivation or state civil servants conduct further research on why incentives do not have a significant effect on the performance of government employees at the North Tapanuli Food Security Service.